2021
DOI: 10.3390/antiox10070999
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Erythrocyte Antioxidant Defense in Colorectal Cancer Patients during Early Postoperative Period: Potential Modifiers and Impact on Clinical Outcomes

Abstract: A better understanding of antioxidant status, its modifiers, and its effect on clinical outcomes in patients undergoing colorectal cancer surgery is needed for effective antioxidant-based interventions. The objectives of this cohort study were: to determine baseline serum (total antioxidant capacity (TAC) and ferric reducing antioxidant power (FRAP); n = 72) and erythrocyte (superoxide dismutase (SOD) and glutathione peroxidase (GPx); n = 47) antioxidant capacity and time-course during the 72 h postoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The role of oxidative stress in cancer has been studied to develop new therapies to inhibit the growth and progression of cancer cells, but also alleviate the symptoms of the disease. Krystek-Korpacka et al monitored serum and erythrocyte antioxidant defenses in a Polish cohort of colorectal cancer patients, during the early postoperative period, to correlate oxidative stress parameters with clinical outcomes [ 11 ]. Based on their data, the authors identified the period between 8 h and 24 h after surgery as the most sensitive period for oxidative homeostasis and positive health outcomes.…”
mentioning
confidence: 99%
“…The role of oxidative stress in cancer has been studied to develop new therapies to inhibit the growth and progression of cancer cells, but also alleviate the symptoms of the disease. Krystek-Korpacka et al monitored serum and erythrocyte antioxidant defenses in a Polish cohort of colorectal cancer patients, during the early postoperative period, to correlate oxidative stress parameters with clinical outcomes [ 11 ]. Based on their data, the authors identified the period between 8 h and 24 h after surgery as the most sensitive period for oxidative homeostasis and positive health outcomes.…”
mentioning
confidence: 99%